Tiger & Bunny. 7 - Nishida, Masafumi (VIZ Media, 2015)
Superpowered humans known as NEXT appeared in the world 45 years ago. Some of them fight crime in the city of Stern Bild while promoting their corporate sponsors on the hit show HERO TV. The people love their superheroes, even if they don't completely understand them, and not all of the NEXT use their powers for good. At Justice Tower, Tiger, Barnaby and Rock Bison confront Jake, but they're no match for his unique powers and take a beating. Meanwhile, Origami Cyclone and Edward head to Jake's secret hideout hoping to capture Kriem and stop the Mad Bears. With the data chip they recover, Saito discovers a way to stop the creepy toys, but the plan requires manpower the team doesn't have. Fortunately, unlikely allies arrive just in time to offer assistance.